2021
DOI: 10.14295/rp.v54i1.233
|View full text |Cite
|
Sign up to set email alerts
|

Early INSURE Therapy Reduces CPAP Failure in Late Preterm Newborns with Respiratory Distress Syndrome

Abstract: Background: INSURE (Intubation, Surfactant administration, and Extubation) therapy is controversial in managing respiratory distress syndrome (RDS) in late preterm newborns. This study aims to determine whether the use of the INSURE in late preterm infants with RDS is associated with improved outcomes compared to similar infants managed with CPAP alone. Methods: A retrospective cohort study compared two different neonatal care units with two different treatments of RDS in late preterm infants in Bucaramanga, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In our analysis, we observed low rates of surfactant use in the delivery room. Early INSURE therapy has been shown to reduce the rate of CPAP failure in infants born at 33 to 36 + 6/7 WG [ 20 ]. In the same way, less invasive surfactant administration (LISA) has been shown to prevent early CPAP failure, even if most of the infants included were < 32 WG [ 21 – 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, we observed low rates of surfactant use in the delivery room. Early INSURE therapy has been shown to reduce the rate of CPAP failure in infants born at 33 to 36 + 6/7 WG [ 20 ]. In the same way, less invasive surfactant administration (LISA) has been shown to prevent early CPAP failure, even if most of the infants included were < 32 WG [ 21 – 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study from 121 preterm infants aged 28 -36 weeks who experienced respiratory distress using NCPAP showed that 36 neonates had respiratory failure (29.7%) with an estimated time of respiratory failure of 60.5 hours. A study by Maria reported that among 57 preterm neonates less than 36 weeks of gestation with respiratory distress receiving (18). Another cohort study showed that among 150 preterm neonates with less than 37 weeks of gestation with respiratory distress receiving NCPAP, 37.8% experienced NCPAP failure in the first 72 hours (16).…”
Section: Discussionmentioning
confidence: 99%